2021
DOI: 10.1007/s10433-021-00613-x
|View full text |Cite
|
Sign up to set email alerts
|

Media representation of older people’s vulnerability during the COVID-19 pandemic in China

Abstract: Older adults have gained great media attention during the COVID-19 pandemic, as they were believed to be vulnerable to the novel virus based on clinical data and epidemiological evidence. The high volume of media coverage played an important role in calling for improved public health services for the older population. Nevertheless, problematic media representations of older people might evoke or amplify ageism during the pandemic. Therefore, drawing on empirical data collected from five mainstream Chinese medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 42 publications
3
28
1
2
Order By: Relevance
“…Participants were asked whether they had encountered five unique messages in the media during the pandemic (e.g., a message that advised older people not to leave their home at all because of COVID‐19, see Supplementary materials ). We developed these items based on other work published during the pandemic (Jen et al., 2021 ) highlighting the ageism that imbued media coverage about older adults and the pandemic (Ayalon et al., 2021 ; Zhang & Liu, 2021 ). Any time participants were asked about messages in “the media,” we directed them to think about examples from all media sources, including newspapers, television, the internet, and the radio, as concurrent research to our own indicated that these messages were omnipresent across media sources internationally (Jen et al., 2021 ; Jimenez‐Sotomayor et al., 2020 ; Meisner, 2021 ; Ng et al., 2022 ); however, we did not ask participants to specify in their responses where they had encountered a particular message.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were asked whether they had encountered five unique messages in the media during the pandemic (e.g., a message that advised older people not to leave their home at all because of COVID‐19, see Supplementary materials ). We developed these items based on other work published during the pandemic (Jen et al., 2021 ) highlighting the ageism that imbued media coverage about older adults and the pandemic (Ayalon et al., 2021 ; Zhang & Liu, 2021 ). Any time participants were asked about messages in “the media,” we directed them to think about examples from all media sources, including newspapers, television, the internet, and the radio, as concurrent research to our own indicated that these messages were omnipresent across media sources internationally (Jen et al., 2021 ; Jimenez‐Sotomayor et al., 2020 ; Meisner, 2021 ; Ng et al., 2022 ); however, we did not ask participants to specify in their responses where they had encountered a particular message.…”
Section: Methodsmentioning
confidence: 99%
“…Since the onset of the COVID-19 pandemic, media representations of older adults have emphasized their physical dependency and frailty ( Jen et al, 2021 ). Older adults have been represented as a homogeneous group based solely upon their chronological age, ignoring their internal diversity ( Zhang & Liu, 2021 ). Similarly, the present analysis found that older adults were frequently represented in an unfavorable but consistent manner, being depicted as a vulnerable group who offer debatable or little value to society.…”
Section: Discussionmentioning
confidence: 99%
“…Within the context of the COVID-19 pandemic, early media analyses of pandemic discourses and portrayals found that older adults were largely represented as a homogenous, biomedically-framed population “at risk” and “vulnerable” to the effects of the virus ( Jen et al, 2021 ; Previtali, Allen, & Varlamova, 2020 ; Zhang & Liu, 2021 ). The media's mention of skilled nursing facilities also tripled in the early stages of the pandemic, focusing attention on staggering infection and death rates ( Miller, Simpson, Nadash, & Gusmano, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between COVID-19 pandemic, ageism and media communication has been analysed in previous studies. An empirical Chinese research, 12 for example, has collected data using mixed method (both qualitative and quantitative) based on content analysis from five mainstream Chinese media outlets. The analyses took into account 568 articles of various types published between 3 January 2020 and 3 May 2020.…”
Section: Ageismmentioning
confidence: 99%